Semiotic approach to the features of the ‘Danube Script’ - Marco Merlini (Documenta Praehistorica, 2005)
The article presents a matrix of basic semiotic markers and rules for examining the internal structure of the sign system developed in the Neo-Eneolithic in the Danube basin. It is intended a) to test the hypothesis that these cultures had an early form of writing, the so-called Danube script; b) to infer the principles of this system of writing; c) to distinguish between bi- and multi-signs texts of the Danube script, without knowing what any of them meant, from compounds of signs associated with other communication codes, among them decoration, symbols, and divinity identifiers. The matrix is applied to some recent discoveries selected not from the core area of the Danube civilization in the Vinča region, but from peripheral regions, in order to document how widespread the Danube script was.